The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1750-3841.14011
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptides Derived from Seaweed Protein and Their Health Benefits: Antihypertensive, Antioxidant, and Antidiabetic Properties

Abstract: Cardiovascular diseases and diabetes are the biggest causes of death globally. Therefore, prevention of these diseases is a focus of pharmaceuticals and functional food manufacturers. This review summarizes recent research trends and scientific knowledge in seaweed protein-derived peptides with particular emphasis on production, isolation and potential health impacts in prevention of hypertension, diabetes and oxidative stress. The current status and future prospects of bioactive peptides are also discussed. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(149 citation statements)
references
References 90 publications
0
130
1
4
Order By: Relevance
“…Analysis of Phytochemicals: Algae has a wide variety of natural pigments like chlorophyll, carotenoids and phycobiliproteins, which exhibit colors ranging from green, yellow, brown and red [39][40][41][42] . The results were corroborated with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of Phytochemicals: Algae has a wide variety of natural pigments like chlorophyll, carotenoids and phycobiliproteins, which exhibit colors ranging from green, yellow, brown and red [39][40][41][42] . The results were corroborated with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The antihypertensive effect exerted by this alga was ascribed to its content in alginates, a polysaccharide that has shown preventive effects in experimental models of hypertension in rats, in addition to their beneficial impact on cholesterol and diabetes mellitus [35,36]. Several studies have described that bioactive peptides and protein hydrolysates from seaweeds have antihypertensive properties [6,37,38], such as those from Undaria pinnatifida [39,40,41], Palmaria palmata [42,43,44], Porphyra columbina [45,46], Porphyra yezoensis [47,48], among others. However, other bioactive compounds found in seaweeds can also contribute to the antihypertensive effect reported for these algae.…”
Section: Hypertensionmentioning
confidence: 99%
“…Therefore, finding safe natural products to replace drugs for alleviating diabetes has become more and more important. It was reported that some active peptides are effective to alleviate diabetes [16][17][18]. Generally, the continuous generation of free radicals in diabetic patients directly leads to the complications of hyperglycemia in various organs due to cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the oxidative system of the damaged cells is restored, it will contribute to attenuate the course of diabetes. The previous researches indicated that CAP had an antioxidant activity [6,17,19], so it is inferred that CAP may have benefits to alleviate diabetes. In order to explore the effective method for curing diabetes, the combined therapeutic effect of CAP and hypoglycemic drugs was also used in this study.…”
Section: Introductionmentioning
confidence: 99%